Marketing Dashboard as an Early Warning on PR. Gagak Hitam - Aang Afandi; Nurafni Eltivia; Siti Holifahtus Sakdiyah (Journal of Applied Business, Taxation and Economics Research, 2022)
The marketing dashboard is one of the company's barometers that can be used for early warning of the company in marketing operations. This study aims to facilitate the company's management and marketing division for decision-making in marketing operational activities by designing a marketing dashboard. The marketing dashboard, apart from being used for decision-making, can also be used for early warning companies in determining steps in the marketing department. The method used in this research is the Research and Development (R&D) method which uses the Analysis, Design, Development, and Implementation, Evaluation (ADDIE) model to design the marketing dashboard. Collecting data using interviews and documentation at the company. This research produces a marketing dashboard that describes sales position, turnover, and stock turnover. The results of the implementation of the marketing dashboard on PR. Gagak Hitam showed a positive response.